CHALLENGES AND PROBLEMS IN THE DEVELOPMENT OF LAND RELATIONS IN BULGARIA - Teodora STOEVA; Violeta DIRIMANOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The implementation of the Common Agricultural Policy after 2007 has brought new dynamic changes to the business environment where this primary Bulgarian industry functions. Getting financial incentives to support income as well as incentives to comply with other European policies distorts the business environment in Bulgaria. The land reform has been a key element of the agricultural transformation during the long-term transition in Bulgaria, which aims to create favourable conditions for the establishment of market economy by decentralizing the process and restoring the right of ownership to all owners and their heirs. The problems related to the study of land relations are of eternal relevance and significance. The importance of land relations is much more essential for the sustainable development of the viable rural regions in Bulgaria, having in mind the favourable natural conditions and the traditions inextricably interwoven with the agricultural sector in the country. The comprehensive research of land relations is a key condition for studying their impact on the socio-economic processes and relations, thus focusing on certain synergistic opportunities for the agricultural sector in Bulgaria. The purpose of this article is to describe, present and analyze the role and challenges of land relations, as well as the related issues that are fundamental for the state of agriculture and the place of the sector in Bulgarian economy as a whole. The study also has a narrow focus on achieving the key goal of intensifying the links between education, business and public authorities in general. For the research analysis we will apply the scientific approach as well as the following methodological framework such as complex and structural analysis. The study focuses on the challenges and problems in the development of land relations in Bulgaria, as well as the range of land relations related to the social, economic, management and legal environment in Bulgaria. The institutional environment in Bulgarian agriculture is a complex system of symbiotic relationships, dynamically changing under the influence of national and sectoral legislation. The challenges and issues of land relations are an extremely complex social phenomenon. The economic, social and environmental influences involved in it has a two-way impact on the agricultural sector. The harmonization and improvement of institutional framework in compliance with the requirements of the EU - development of sectoral legislation, re-structuring of agricultural farms, as well as various aspects of the implementation of the CAP, competitiveness and development of rural regions, are part of the issues and challenges related to the sustainable development of land relations and the agricultural sector in Bulgaria.